RETRACTED: USP22 Protects Against Myocardial Ischemia–Reperfusion Injury via the SIRT1-p53/SLC7A11–Dependent Inhibition of Ferroptosis–Induced Cardiomyocyte Death - Ma, Shuxian; Sun, Linyan; Wu, Wenhao; Wu, Jiangli; Sun, Zhangnan; Ren, Jianjun (Frontiers in Physiology, 2020)
Myocardial ischemia-reperfusion (MI/R) injury is characterized by iron deposition and reactive oxygen species production, which can induce ferroptosis. Ferroptosis has also been proposed to promote cardiomyocyte death. The current study sought to define the mechanism governing cardiomyocyte death in MI/R injury. An animal model of MI/R was established by ligation and perfusion of the left anterior descending coronary artery, and a cellular model of IR was constructed in cardiomyocytes. ChIP assay was then conducted to determine the interaction among USP22, SIRT1, p53, and SLC7A11. Loss- and gain-of-function assays were also conducted to determine the in vivo and in vitro roles of USP22, SIRT1, and SLC7A11. The infarct size and pathological changes of myocardial tissue were observed using TCC and H&E staining, and the levels of cardiac function- and myocardial injury- related factors of rats were determined. Cardiomyocyte viability and apoptosis were evaluated in vitro, followed by detection of ferroptosis-related indicators (GSH, reactive oxygen species, lipid peroxidation, and iron accumulation). USP22, SIRT1, and SLC7A11 expressions were found to be down-regulated, whereas p53 was highly-expressed during MI/R injury. USP22, SIRT1, or SLC7A11 over-expression reduced the infarct size, ameliorated pathological conditions, cardiac function, as evidenced by reduced maximum pressure, ejection fraction, maximum pressure rate, and myocardial injury characterized by lower CPK and LDH levels in vivo. Moreover, USP22, SIRT1, or SLC7A11 elevation contributed to enhanced cardiomyocyte viability and attenuated ferroptosis-induced cell death in vitro, accompanied by increased GSH levels as well as decreased reactive oxygen species production, lipid peroxidation, and iron accumulation. Together, these results demonstrate that USP22 over-expression could inhibit ferroptosis-induced cardiomyocyte death to protect against MI/R injury via the SIRT1/p53/SLC7A11 association.